2018
DOI: 10.12659/msm.910012
|View full text |Cite
|
Sign up to set email alerts
|

Salmon Calcitonin Attenuates Degenerative Changes in Cartilage and Subchondral Bone in Lumbar Facet Joint in an Experimental Rat Model

Abstract: BackgroundFacet joint degeneration (FJD) is one of the common causes of low back pain (LBP), and estrogen deficiency is one of the triggers for FJD. Calcitonin may possess the potential for treating osteoarthritis, but to date the hormone has not been studied in the treatment of FJD. Therefore, the aim of this study was to investigate the effects of salmon calcitonin (sCT) on FJD induced by estrogen deficiency after ovariectomy (OVX).Material/MethodsThirty female Sprague-Dawley rats were randomly assigned to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(53 reference statements)
2
8
0
Order By: Relevance
“…However, it is interesting that the degenerative cartilage changes in OVX rats were mainly manifested as small fissures confined to the surface, and did not extend to the deeper cartilage, indicating relatively modest cartilage lesions compared with those secondary to mechanical instability or chemical stimulation [3739]. Our findings are consistent with previous studies, in which the main feature of FJ cartilage degeneration was loss of thickness, but not damage to superficial cartilage [40,41], thereby supporting the hypothesis that estrogen can prevent cartilage loss. Based on the present findings and those from previous studies, we conclude that estrogen deficiency stimulated subchondral bone remodeling with resultant deterioration of the subchondral bone microarchitecture and thus impaired the biomechanical properties, and also led to high cartilage turnover with increased chondrocyte apoptosis and catabolic metabolism, which finally caused the cartilage degeneration in this model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it is interesting that the degenerative cartilage changes in OVX rats were mainly manifested as small fissures confined to the surface, and did not extend to the deeper cartilage, indicating relatively modest cartilage lesions compared with those secondary to mechanical instability or chemical stimulation [3739]. Our findings are consistent with previous studies, in which the main feature of FJ cartilage degeneration was loss of thickness, but not damage to superficial cartilage [40,41], thereby supporting the hypothesis that estrogen can prevent cartilage loss. Based on the present findings and those from previous studies, we conclude that estrogen deficiency stimulated subchondral bone remodeling with resultant deterioration of the subchondral bone microarchitecture and thus impaired the biomechanical properties, and also led to high cartilage turnover with increased chondrocyte apoptosis and catabolic metabolism, which finally caused the cartilage degeneration in this model.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study demonstrated that COMP is also a biomarker for FJ degeneration in OVX rats [41]. The present study confirmed that the serum COMP concentration was negatively correlated with cartilage thickness.…”
Section: Discussionsupporting
confidence: 88%
“…sCT can inhibit the progression of facet joint syndrome in ovariectomized rats. This potential is ascribed to the inhibitory impacts of sCT on apoptosis, cartilage metabolism imbalance, and bone remodeling (24). PCR analysis shows that the chronic constriction injury causes the upregulation of tetrodotoxin-sensitive Nav.1.3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the slides were counterstained with hematoxylin. The results were expressed as an average intensity of optical density (IOD/mm 2 ), according to the method previously described [20,21].…”
Section: Methodsmentioning
confidence: 99%